STIGMA MASKULINITAS DI TENGAH BUDAYA PATRIARKI ANALISIS TEORI SOLIDARITAS SOSIAL EMILE DURKHEIM - Jauzaa Hayaah Kusnandar (LPPM Universitas Negeri Surabaya, 2023)
atriarchal culture is a culture that is still closely held by the Indonesian people, society in a patriarchal culture see the position of men as higher than women with all the domination and stigma of masculinity attached. However, the existence of a patriarchal culture does not always benefit men and harm women. With all the stigma of masculinity that exists, men receive a heavy burden because men tend not to have gaps. A case of sexual violence and bullying emerged to the public at the end of 2021 after the story went viral on social media. Victims share stories of harassment and bullying perpetrated by fellow male perpetrators who also worked at the central KPI office in 2015. In this study, the researchers aimed to analyze how large the violence number against men is and to reveal the emotional, physical, and mental burdens possessed by men. Men for the stigma they receive. the method used in this research is descriptive qualitative with interview data collection techniques conducted on 9 male respondents aged 19-22 years. This study also uses the theory of social solidarity by Emile Durkheim. Additional data is also needed and obtained from literature sources in national journals, international journals, and local news articles. The data analysis technique uses analysis techniques by Miles and Huberman, namely interactive data analysis techniques through 4 stages: 1) data collection stages, 2)reduction stages, 3) data presentation stage, and 4) conclusion drawing stage. The result of the study prove that very few men who experience domestic violence or sexual violence report out of shame, victim of violence and bullying from the central KPI also feel the same way. The victim receives a lot of burdens, especially having to bear the stereotype as a man, husband, and father where he has to be a strong individual. Interviews prove that men feel pressured by the stigma of masculinity in the community, so they feel more comfortable expressing themselves in their immediate environment, such as family or close friends. Keywords: Sexual Violence; Bullying; Masculinity Stigma